Tradisi Hitung Waris dalam Walimatul ‘Ursy Masyarakat Melayu - Yuliatin, Yuliatin; Nabilah Effendi, Ghina; Sibawaihi, Muhammad; Santri, Diah Dwi; Septia Utami, Henny (Institut Agama Islam Negeri Curup, 2025)
The tradition of calculating inheritance in walimatul ‘ursy of Jambi Malay community is a social practice that regulates the recording of wedding donations as a form of debt that must be returned in the future. This tradition reflects a reciprocity system that aims to maintain the family's economic balance, but also creates a financial burden for the next generation. This study aims to analyse the tradition of inheritance calculation from the perspective of Maqāṣid al-Syarī'ah, to assess whether this practice is in accordance with the principles of justice and benefit in Islamic law. This research uses a qualitative approach with the method of sociology of Islamic law. Data were collected through in-depth interviews with traditional leaders, scholars, and people involved in this tradition, as well as participatory observation of the practice of calculating inheritance in weddings. Data analysis techniques included data reduction, data presentation, and conclusion drawing based on Maqāṣid al-Syarī'ah theory and Islamic economic principles related to qardh (debt and credit) and sadd al-dharī'ah (prevention of harm). The results show that although the tradition of calculating inheritance has positive aspects in strengthening social relations and helping to finance weddings, this practice also has the potential to create economic pressures that are not in accordance with the principles of Maqāṣid al-Syarī'ah, especially in the aspects of ḥifẓ al-māl (protection of property) and ḥifẓ al-nafs (protection of the soul). This tradition can cause intergenerational financial burden if it is not regulated with a more flexible and transparent mechanism. Therefore, it is necessary to reformulate the practice of inheritance calculation in order to maintain its social values without causing excessive economic burden for individuals and families.